Efektivitas Kebijakan Moneter Bank Indonesia dalam Meningkatkan Akses Layanan Perbankan Syariah - Eneng Siti Sutihat; Hasan Bulqiah; Rasidah Novita Sari (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
Sharia-based monetary policy instruments, such as the Bank Indonesia Sharia Certificate (SBIS) and the Sharia Interbank Money Market (PUAS), contribute significantly to liquidity stability and expand access to sharia banking services. Even though the sharia banking sector continues to grow, the market share of the national banking industry is still relatively small due to low financial literacy, limited infrastructure and global economic challenges. This research highlights the importance of strengthening sharia financial literacy, developing digital infrastructure, as well as collaboration between the government, private sector and Bank Indonesia to overcome these obstacles. Strategic recommendations are provided to increase sharia-based financial inclusion which is expected to become a model for countries where the majority of the population is Muslim.